Personnel human resource management : - Milkovich, George T. (Business Publications, 1988)
"Human Resource Management, Eighth Edition", continues to present both the theoretical and practical aspects of HRM. The theoretical material is presented throughout the text and highlighted via a marginal glossary. The practical aspects of HRM are presented through lively and pedagogically effective examples woven throughout the text and in the end-of-chapter materials. The new edition reflects changes in the business world in general, and the HRM function within organizations, since the previous edition was published.